Impact of Socioeconomic Factors on Outcome of Total Knee Arthroplasty - Barrack, Robert L. (Springer US, 2013)
BACKGROUND: Few data exist regarding the impact of socioeconomic factors on results of current TKA in young patients. Predictors of TKA outcomes have focused primarily on surgical technique, implant details, and individual patient clinical factors. The relative importance of these factors compared to patient socioeconomic status is not known. QUESTIONS/PURPOSES: We determined whether (1) socioeconomic factors, (2) demographic factors, or (3) implant factors were associated with satisfaction and functional outcomes after TKA in young patients. METHODS: We surveyed 661 patients (average age, 54 years; range, 18–60 years; 61% female) 1 to 4 years after undergoing modern primary TKA for noninflammatory arthritis at five orthopaedic centers. Data were collected by an independent third party with expertise in collecting healthcare data for state and federal agencies. We examined specific questions regarding satisfaction, pain, and function after TKA and socioeconomic (household income, education, employment) and demographic (sex, minority status) factors. Multivariable analysis was conducted to examine the relative importance of these factors for each outcome of interest. RESULTS: Patients reporting incomes of less than USD 25,000 were less likely to be satisfied with TKA outcomes and more likely to have functional limitations after TKA than patients with higher incomes; no other socioeconomic factors were associated with satisfaction. Women were less likely to be satisfied and more likely to have functional limitations than men, and minority patients were more likely to have functional limitations than nonminority patients. Implants were not associated with outcomes after surgery. CONCLUSIONS: Socioeconomic factors, in particular low income, are more strongly associated with satisfaction and functional outcomes in young patients after TKA than demographic or implant factors. Future studies should be directed to determining the causes of this association, and studies of clinical results after TKA should consider stratifying patients by socioeconomic status. LEVEL OF EVIDENCE: Level III, therapeutic study. See Instructions for Authors for a complete description of levels of evidence.